CHILD CUSTODY AND ACCESS DURING PANDEMIC: BEING IN THE LIMELIGHT - Anis Shuhaiza Md Salleh; Ain Husna Mohd Arshad, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Covid-19 Pandemic has affected human life socially, economically, and politically where their movement and activities have been restricted. The well-being of family institutions is among the most important aspects that are significantly affected by the pandemic. Issues surrounding custody, visitation, and access over a child involving divorced or separated parents may invite disputes between parties if not amicably resolved. By using a qualitative analysis of library-based sources and interviews, this article attempts to highlight the issues relating to custody and access orders in response to the pandemics. It is found that the traditional court order on custody and access over a child remains enforceable until a variation order pertaining to the same has been made. Nevertheless, during the Movement and Control Order (MCO) or other administrative movement control such as the Enhanced Movement Control Order/Tightened Movement Control (EMCO/PKPD) and Targeted Enhanced Movement Control Order (TEMCO), where the operation of the court is limited or rather suspended, the existing orders seemed to be impractical to certain extent particularly in-person access or shared parenting time where the child will get time to be physical with the father and mother. In the end, recommendations are posted for the betterment of parties in facing the issue.